2023
DOI: 10.1039/d3cs00063j
|View full text |Cite
|
Sign up to set email alerts
|

Nanoprobe-based molecular imaging for tumor stratification

Xianbin Ma,
Mingchuan Mao,
Jiaqi He
et al.

Abstract: This review highlights the use of nanoprobes to stratify various therapeutic modalities and provides an outlook on the challenges and future directions of nanoprobes for patient stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 384 publications
(567 reference statements)
0
12
0
Order By: Relevance
“…This facilitates the visualization and monitoring of cellular behavior under biological conditions or in response to specific modulators. [10,11] Metabolic glycoengineering allows for the chemical modification of the cell membrane, generating bioorthogonal functional groups on cell-surface glycans through intrinsic biosynthetic pathways. These groups then undergo covalent reactions with exogenous counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…This facilitates the visualization and monitoring of cellular behavior under biological conditions or in response to specific modulators. [10,11] Metabolic glycoengineering allows for the chemical modification of the cell membrane, generating bioorthogonal functional groups on cell-surface glycans through intrinsic biosynthetic pathways. These groups then undergo covalent reactions with exogenous counterparts.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Their efficiency as RNA delivery systems has been well-documented in numerous reports, garnering widespread attention. 10 , 11 Typically, LNPs formulation consists of phospholipids, cholesterol, PEGylated lipids, and key lipids. Phospholipids enhance the cellular uptake of LNPs, while cholesterol, a natural component of the cell membrane, improves LNPs stability by filling intervals between lipids and promoting fusion with endosomal membranes upon uptake.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, chimeric antigen receptor macrophage (CAR-M) technology has been emerging as a means to engineer bystander M2 macrophages to repolarize into M1 macrophages by pro-inflammatory cytokines and chemokines . In line with the critical role of macrophages in tumor immunotherapy, numerous studies have demonstrated that macrophages play a critical role in the prognosis of tumor treatments associated with immune responses. It is thus appealing to understand the M1/M2 macrophage polarization for better illustrating the immune responses in the tumors during cancer treatments.…”
Section: Introductionmentioning
confidence: 99%